Oxygen and wound care: A review of current therapeutic modalities and future direction. Issue 4 (11th June 2013) - Howard, Michael A.; Asmis, Reto; Evans, Karen Kim; Mustoe, Thomas A.
Abstract While the importance of oxygen to the wound healing process is well accepted, research and technological advances continue in this field and efforts are ongoing to further utilize oxygen as a therapeutic modality. In this paper, the authors briefly review the role of oxygen in wound healing and discuss the distinct mechanism of action as well as the advantages and disadvantages of the three major oxygen‐based therapies currently in clinical use (Hyperbaric Oxygen and Topical Oxygen and Continuous Diffusion of Oxygen), as well as review the existing literature regarding these distinct therapeutic modalities.